Investigating the Impact of AI-Powered Digital Educational Platforms on Students’ Learning and Teachers’ Practice in Abu Dhabi Schools - ALYAMMAHI, AISHAH (2020)
Abstract The purpose of this study is to shed light on the investigation of the impact and influence of AI-powered digital learning platforms on student learning and teacher practice and to show the role of these platforms amidst the COVID-19 pandemic. The study also proposes the best practices of using AI-enabled learning platforms for both the student and the teacher to achieve the learning outcomes and improve student learning. To measure this impact, the researcher applies the mixed method approach – qualitative and quantitative – to arrive at comprehensive, accurate and reliable findings. The research sample consists of 7039 students in 12 public schools and 512 teachers in schools across the Emirate of Abu Dhabi in the UAE. The sample is divided into two groups, where one group started implementing the Alef Platform a year ahead of the other group. The thesis presents evidence of the difference in the performance between those two groups and found a positive correlation between students' learning and engagement with the Alef Platform and the results they achieved. Moreover, the thesis shows that activating the Alef Platform helped develop the teachers’ performance, reduced their workload and transformed their role from traditional instructors into facilitators and coaches. This thesis also asserts the importance of professional development for teachers and school administrators and recommends them to continue training to be able to fully utilize the features of such platforms. The researcher also proposes that Alef Platform adds the remaining school subjects and that the Platform is defined as a national and global project inclusive of all school subjects from grade 1 up to grade 12, with the aim of creating a comprehensive virtual learning ecosystem to support and ensure the continuation and sustainability of learning in cases of natural disasters anywhere around the world.